Spiritual Emotional Freedom Technique (SEFT) training as a solution to anxiety in the midst of COVID-19 pandemic - Nadia Oktiffany Putri; Narita Diatanti (Universitas Muhammadiyah Magelang, 2022)
The Covid-19 pandemic has now spread to practically every region of the globe, including the Malang Regency. The psychological influence in the form of anxiety is the one that is felt most directly. As a result, community service activities on the theme of anxiety management using SEFT therapy are carried out in order to maintain public health, particularly in the psychological aspect. The coordination step precedes the implementation stage, which is followed by the evaluation stage. This service activity yielded positive effects, as shown by the participants' greater comprehension. This service initiative is expected to alleviate the community's anxiety in the occurrence of a pandemic.